Prevalence of musculoskeletal disorders in subjects not exposed to biomechanical overload - Stucchi, Giulia; Cairoli, Silvia; Crapanzano, Rossana; Basilico, Stefano; Leocata, Giuseppe; Battevi, Natale (La Medicina del Lavoro, 2018)
Background: Data on the prevalence of work-related musculoskeletal disorders (WMSDs) in groups of unexposed subjects may serve for comparison in studies on risk/damage in groups of exposed subjects and for the planning of preventive interventions. Objectives: To assess the musculoskeletal health status in a group of working subjects not exposed to biomechanical overload. Methods: Medical histories were collected by occupational health physicians as part of an active health surveillance program. An ad hoc questionnaire was administered to the subjects to detect musculoskeletal disorders. Results: The sample consisted of 1023 subjects (605 females and 418 males) with a mean age of 40 years. The prevalence of acute low back pain and disc hernia was 4% and 5.6% respectively; 4.3% of subjects were affected by at least one disorder of the upper limbs while the prevalence of knee disorders was 1.7%. Standardized data proved to be in line with previous studies with the exception of a greater prevalence of shoulder disorders and disc hernia. Conclusions: WMSDs occur ubiquitously across the general working population unexposed to biomechanical overload. Such findings represent a valid reference for groups of exposed working subjects, in that any excess of such disorders/pathology may be due to specific work conditions.